SISTEM DAN PROSES DALAM PILKADA LANGSUNG: Problem Mobilisasi Dukungan - Yulianti, Reny; Frihatin, Diny (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2018)
Efforts to realize a free, democratic,direct, fair and transparent, at least, there are three thingsneeds to be done. First, government regulation no. 6/2005as the implementation of Law no. 32/2004 needs to be followed and criticizedcontinue to avoid off the right rails. Second, themembers of parliament and political figures who became actorssupport mobilization should not be selfishmyself and his group. Third, there needs to be an equationperceptions, commitments and steps to make Pilkadasung not justbecome a legal way of legitimizing the power to be gained,but more important is how they are afterelected as a couple Kada / Wakada can be more capablepromoting and prospering the community, in particularvillagers.